Respuestas
Respuesta dada por:
40
Factorizando resultaría:
![24a^2xy^2-36x^2y^4=12xy^2(2a^2-3xy^2) 24a^2xy^2-36x^2y^4=12xy^2(2a^2-3xy^2)](https://tex.z-dn.net/?f=24a%5E2xy%5E2-36x%5E2y%5E4%3D12xy%5E2%282a%5E2-3xy%5E2%29)
Saludos c:
Saludos c:
Respuesta dada por:
63
Factorizar.
24a²xy² - 36x²y⁴ = Sacamos factor comun 12xy²
12xy²(2a² - 3xy²)
Respuesta.
12xy²(2a² - 3xy²)
24a²xy² - 36x²y⁴ = Sacamos factor comun 12xy²
12xy²(2a² - 3xy²)
Respuesta.
12xy²(2a² - 3xy²)
Preguntas similares
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años